Hypermedia: Support for a more natural information organization - Bannon, Liam J.; Grønbæk, Kaj (DAIMI Report Series, 1989)
This paper gives an introduction and an overview of an emerging technology denoted Hypermedia. The technical capabilities of current systems are briefly described along with examples of usage. Based on our own experiences with Hypermedia systems we give a more detailed discussion of the use of Hypermedia for: authoring, organization and presentation of information, and sharing of information in a community. Finally some obstacles to the success of Hypermedia applications are discussed.